Comparison of Semidistributed Multinode TOA-DOA Fusion Localization and GPS-Aided TOA (DOA) Fusion Localization for MANETs. (30th December 2008) - Wang Wang, Zhonghai Zhonghai; Zekavat Zekavat, Seyed Seyed
Abstract : This paper evaluates the performance of a semidistributed multinode time-of-arrival (TOA) and direction-of-arrival (DOA) fusion localization technique in terms of localization circular error probability (CEP). The localization technique is applicable in mobile ad hoc networks (MANETs) when global positioning system (GPS) is not available (GPS denied environments). The localization CEP of the technique is derived theoretically and verified via simulations. In addition, we theoretically derive the localization CEP of GPS-aided TOA fusion and GPS-aided DOA fusion techniques, which are also applicable in MANETs. Finally, we compare these three localization techniques theoretically and via simulations. The comparison confirms that in moderate scale MANETs, the multinode TOA-DOA fusion localization technique achieves the best performance; while in large scale MANETs, GPS-aided TOA fusion leads to the best performance.